2020
DOI: 10.3390/life10100243
|View full text |Cite
|
Sign up to set email alerts
|

Quercitrin Ameliorates Hyperlipidemia and Hepatic Steatosis in Ovariectomized Mice

Abstract: Nonalcoholic fatty liver disease (NAFLD) is associated with progressive metabolic diseases. Estrogen deficiency increases the NAFLD risk among postmenopausal women. Thus, effective agents to prevent and treat NAFLD in postmenopausal women are required. Quercitrin (Quer) is a natural glycosylated flavonoid with antimicrobial, anti-inflammatory, and hypolipidemic effects. This study investigated whether Quer improves dysregulated lipid metabolism and suppresses hepatic steatosis in ovariectomized (OVX) mice as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 36 publications
1
11
1
Order By: Relevance
“…Flavonoids and their derivatives are a class of natural compounds with abundance within the plant kingdom that exert versatile bioactivity including anti-diabetic and antiobesity effects (Lee et al, 2017;Hussain et al, 2020;Li et al, 2020;Huang et al, 2021). The beneficial properties of the flavonoids and flavonoid glycosides in diabetes and obesity management are achieved via modulation in targeted signaling networks such as the IRS/PI3K/AKT/GLUT4 pathway, thereby improving glucose metabolism, and glucose transport or aldose reductase by carbohydrate metabolic pathways in pancreatic β-cells, hepatocytes, adipocytes and skeletal myofibers (Goto et al, 2012;Lee et al, 2017;Hur et al, 2020;Hussain et al, 2020;Li et al, 2020;Wu et al, 2020;Huang et al, 2021). However, a frequently reported obstacle for the use of flavonoids in vivo is their limited bioavailability (Hussain et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Flavonoids and their derivatives are a class of natural compounds with abundance within the plant kingdom that exert versatile bioactivity including anti-diabetic and antiobesity effects (Lee et al, 2017;Hussain et al, 2020;Li et al, 2020;Huang et al, 2021). The beneficial properties of the flavonoids and flavonoid glycosides in diabetes and obesity management are achieved via modulation in targeted signaling networks such as the IRS/PI3K/AKT/GLUT4 pathway, thereby improving glucose metabolism, and glucose transport or aldose reductase by carbohydrate metabolic pathways in pancreatic β-cells, hepatocytes, adipocytes and skeletal myofibers (Goto et al, 2012;Lee et al, 2017;Hur et al, 2020;Hussain et al, 2020;Li et al, 2020;Wu et al, 2020;Huang et al, 2021). However, a frequently reported obstacle for the use of flavonoids in vivo is their limited bioavailability (Hussain et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies reported that AST regulated lipogenesis and fat accumulation in 3T3-1L adipocytes via suppression of the mRNA expression of PPARγ, C/EBPα, FASN and leptin (Swamy et al, 2020;Wu et al, 2020). Similarly, QUE demonstrated significant effect against liver fat accumulation and decreased inflammatory markers in different liver injury models (Roman Junior et al, 2015;Hur et al, 2020). Based on their presence in the ALM extract and the data suggesting potential to influence lipid accumulation in several experimental models, we have targeted for our present investigation AST and QUE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it could suppress airway inflammation via the inhibition of MAPK [ 53 ]. In addition, quercitrin decreased the risk of acetaminophen-induced acute liver toxicity in mice [ 54 ]. Moreover, quercitrin and quercetin reduced the occurrence of inflammatory response and oxidative stress in macrophages [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The flavonoid heteroside quercitrin (quercetin-3-O-ramnoside) ( 94 ) was isolated from S. rebaudiana as documented in the Stevia genus [ 1 ]. The biological activity of this compound has been extensively studied through the years, involving anti-inflammatory activity determined by Camuesco et al [ 235 ], antiproliferative and proapoptotic effects by Cincin et al [ 236 ], anti-Dengue virus 2 [ 237 ], osteoporosis attenuation [ 238 ], hair growth stimulation [ 239 ], improvement of hyperlipidemia and hepatic steatosis in ovariectomized mice [ 240 ], and inhibition of α-glicosidase [ 241 ]. Like other flavonoids discussed in this update, quercitrin was reviewed by Boniface and Ferreira et al [ 176 ], showing antiprotozoal activity against P. falciparum (43.4% inhibition after 48 h), inhibitory effects on L. amazonensis arginase (IC 50 = 10.0 µM), and activity against Dengue virus 2 (DENV-2 NS2B) (IC 50 = 43.6 µM) and Dengue virus 3 (DENV-3 NS2B) (IC 50 = 32.0 µM).…”
Section: Biological Activitymentioning
confidence: 99%